MODEL OF DENGUE SPREADING IN MALANG DISTRICT AND MALANG CITY USING CLIMATE FACTOR - Nailah, Nada
Dengue Hemorrhagic Fever is a disease transmitted through an intermediary of mosquitoes. Indonesia is reported as the 2nd country with the largest dengue cases among 30 endemic regions. In 2017, the highest number of DHF events occurred in 3 provinces in Java, namely West Java, East Java, and Central Java with the highest mortality rates occurring in East Java Province with one of the factors is climate change. Therefore, making the early detection model of Dengue distribution is considered necessary, especially in areas that contribute a lot of dengue cases, for example in Malang City and Malang District. Poisson, negative binomial, and logistic regression model will be used to know the relationship between DHF incidence and climate factor using unit of month. Based on the simulation results, it was found three information; the lower temperature and rainfall, and the higher humidity can cause a higher incidence of DHF, then there is a temperature, rainfall, and humidity that can cause DHF events above the average value DHF occurrences per year called the climate threshold, and the last is the threshold temperature, rainfall, and humidity of Malang Regency and Malang City has a different value.